2011
DOI: 10.1111/j.1751-2980.2011.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors that predict the requirement of aggressive therapy among Chinese patients with Crohn's disease

Abstract: OBJECTIVES:  Crohn's disease is now increasingly considered as a disabling disease. Conventionally, the disease is managed by step‐up therapy. In recent years, the top‐down strategy has been proposed and is thought to benefit the patients in whom the condition is likely to rapidly deteriorate toward disabling. However, this strategy has severe adverse effects which have to be weighed against its benefits. The aim of this study is to identify the risk factors that can predict the requirement of top‐down therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 27 publications
2
34
0
1
Order By: Relevance
“…The efficacy of ~1.0 mg/kg AZA in maintaining remission of CD was confirmed. Next, we compared the effect of <1.0 mg/kg AZA with that of 1.0-2.0 mg/kg AZA at 24 months, based on our previous result that the severity of disease remained unaltered in 90% patients with CD during the 2-year period [17]. To our surprise, the remission rate in patients of <1.0 mg/kg group was significantly higher than that in those of 1.0-2.0mg/kg group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of ~1.0 mg/kg AZA in maintaining remission of CD was confirmed. Next, we compared the effect of <1.0 mg/kg AZA with that of 1.0-2.0 mg/kg AZA at 24 months, based on our previous result that the severity of disease remained unaltered in 90% patients with CD during the 2-year period [17]. To our surprise, the remission rate in patients of <1.0 mg/kg group was significantly higher than that in those of 1.0-2.0mg/kg group.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, higher rates of relapse were seen in female patients; their doses of AZA had to be escalated. Older age was another factor for long-term remission and young patients were prone to be disabling CD [17,19-21]. Patients in <1.0 mg/kg group were significantly older than those in 1.0-2.0 mg/kg group at the start of AZA therapy, and the age (35.5 years) was almost the same as that reported by Fraser AG et al, who observed a lower relapse rate in the patients above 36 years of age [19].…”
Section: Discussionmentioning
confidence: 99%
“…A study from China 171 has identified similar risk factors for developing disabling disease as in the West, namely age < 40 years at diagnosis, steroid requirement for treating acute exacerbation and perianal disease at diagnosis 109,161 …”
mentioning
confidence: 99%
“…[4][5][6][7][8]18 Smoking has also been associated with the development and progression of CD, 6,8,[12][13][14]18 increasing the risk for IBD-related surgery. Similarly, perianal disease is associated with an increased risk of progressive complicated CD [8][9][10][11] and resectional surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics and outcomes may inform the clinician as to the therapeutic strategy to adopt, for example early aggressive therapy for those patients who are most likely to progress to surgery. 2,3 A range of factors have been associated with an increased risk of complicated (stricturing and penetrating) CD behaviour including the specific NOD2 genotypes [4][5][6] having had perianal disease [8][9][10][11] and cigarette smoking. 1,6,8,[12][13][14] Complicated disease is strongly associated with a requirement for surgery 15 ; therefore, knowledge of such genetic, environmental and clinical predictors may guide clinicians in developing a personalised approach for individual patients.…”
Section: Introductionmentioning
confidence: 99%